Cassidy Gibson: capstone - Gibson, Cassidy, artist (Colorado State University. Libraries, 2018)
The artist's statement: I believe that the inspiration of my work is rooted in two words that have rung true for me from an early age: kinship and communion. One of the most paramount places that has remained a consistent home for these two words is the kitchen table. For me, the kitchen table has been this beautiful and wildly chaotic culmination of friendship, hard work, rest, nourishment, communion and kinship. It's such an important place because one of the collective experiences that we all participate in as humans is the act of sharing a meal with another. The table looks differently for everyone - and it may not even look like a table at all - but the act of sitting and eating together holds a familiarity to all. There's something profound that happens when people gather around the table - eating and passing food from their own tableware - and I want my work to be an intimate part of these profound moments. My pots are nothing but a continuation of what humans have been doing for thousands of years - making functional pieces for the home. I want to design pots that are simple in color and shape and can be best used as a functional tabletop object. I focus on how the formal qualities of the piece can pair well with the food and drink that it's holding, while also not getting caught up on how perfected the rims, feet, and curvatures need to look. The questions I do ask myself follow the relationship between the food and the pots. How can the surface of the plate enhance the color of the pasta? How can I make a bowl that is pleasant to scoop ice cream out of? How can I make a handless cup that's not too heavy, but also thick enough so that the coffee won't burn your hands? These are the problems that I attempt to solve throughout the process, and my hope is that they will encourage a body of work that helps to curate meaningful moments around your own table. It's not only the tangible qualities of a cup or a bowl that make it such a remarkable object, rather, the settling of the clay and communion of people into the moment together. The social sipping out of the cups, the meals shared with serving bowls, the witnessing of a bloom from the flower vase - these moments are all so precious, and they're important. Sitting around the kitchen table, participating in the communion and kinship with others, is important. It is then that these vessels become more than just pieces of clay from the ground; they're now the tangible manifestation of the intangible sentiment of a moment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery